Evaluation of HBV Antibody Levels among Students at the Libyan International University: A Cross-Sectional Study - Elsaid, Amina; Abusedra, Amina; Abbas , Ghada; Ahweidi, Salma; Eltboli, Nagelah; Alhasi, Mariam (AlQalam Journal of Medical and Applied Sciences, 2026)
Hepatitis B virus (HBV) remains a global public health concern, particularly among healthcare professionals and medical students who face increased risk of occupational exposure. Although vaccination provides initial protection, anti-HBs antibody levels may decline over time, potentially compromising immunity. This study aimed to evaluate the levels of hepatitis B surface antibodies (anti-HBs) among medical students at the Libyan International University (LIU). A cross-sectional study was conducted from January to April 2025 involving 72 medical students who had completed the full HBV vaccination series. Venous blood samples were analyzed to measure anti-HBs titers. Protective immunity was defined as anti-HBs levels ≥10 IU/mL. A total of 72 students, of whom 55 (76.4%) were females and 17 (23.6%) males. The mean ages were 20.8 ± 1.4, median 21 years. The majority, 56 (77.8%) of students are in Applied Medical Science. The study reported that anti-HBs antibody titers were a wide range from 0.2 to 52 mIU/mL with a mean of 9.7± 13.1, median = 2.77. About 50 (69.4%) were less than 10 IU/mL, which means they had no immunity, while 22(30.6%) had equal to or more than 10 IU/mL, considered as immune. The findings reported that there were no statistical differences between the students according to age, gender, or academic year. The findings indicate that despite full vaccination, a significant number of medical students do not retain protective antibody levels. This highlights the need for post-vaccination monitoring and consideration of booster doses, particularly among high-risk groups such as medical trainees.